The impact of cohabitation on the character Todd Gilbert in A.S.A Harrison’s The Silent Wife - Fikih Pramudana; Ni Made Widisanti Swetasurya; Shita Dewi Ratih Permatasari (Universitas Pakuan, 2025)
The practice of living together without marriage is common in some communities. Marriage serves to legalize the relationship between men and women, allowing them to share a home legally. The term